Déracinement au féminin et quête de soi - Carmen ANDREI; Nicoleta DIMA (OUSTRIC) (ACROSS)
In this article, we address the question of women living the experience of exile: chosen or suffered.  There are many reasons for abandoning families and countries for an indefinite period. Nevertheless, we know for a fact that it is a quest whose goal is to access a better life. Migration and its geopolitical impacts have always been a favourite subject for researchers without giving the same importance to the situation of women living this trying experience. However, the problem of the latter represents a subject of general interest that has long been obscured in a context where they are the main victims of psychological or physical abuse. Our corpus is made up of the testimonies of women aiming for professional integration, met during the FLE classes that we provide, and this article represents the joint reflection, with two different perspectives on the question, of a thesis coordinator and her PhD student.